The Influence of Digital Competence, Digital Literacy, and Emotional Intelligence on Teacher Performance (Case Study at Senior High School 14, Tangerang City) - Kurniawan, Raihan; Kuncoro, Aris Wahyu (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the influence of digital competence, digital literacy, and emotional intelligence on teacher performance within a public high school in Tangerang. The research employs a quantitative approach using a survey method, with teachers as the respondents, analyzed through multiple linear regression. Findings demonstrate that digital competence, digital literacy, and emotional intelligence each exert a positive and significant effect on teacher performance. Collectively, these factors also contribute to strengthening overall professional effectiveness in the classroom. The study underscores the growing importance of integrating digital skills with emotional intelligence to enhance teacher adaptability and resilience in meeting the demands of contemporary education. Practical implications suggest that schools should provide continuous professional development focusing on technological capacity building and soft skills reinforcement. The study contributes to the literature by highlighting the complementary roles of digital and emotional competencies in shaping sustainable teacher performance.